Non-catalytic pyrolysis of ethane to ethylene in the presence of CO2 with or without limited O-2 - Choudhary, Vasant R.; Mondal, Kartick C.; Mulla, Shafeek Abdul Rashid (Journal of Chemical Science, 2006)
Influence of the presence Of CO2, which is a mild oxidant, on the performance of the thermal cracking of ethane to ethylene in the absence or presence of limited O-2 at different temperatures (750-900 degrees C), space velocities (1500-9000 h(-1)) and CO2/C2H6 and O-2/C2H6 mole ratios (0-2.0 and 0-0.3 respectively) has been investigated. In both the presence and absence of limited 02, ethane conversion increases markedly because of the presence Of CO2, indicating its beneficial effect on the ethane to ethylene cracking. The increased ethane conversion is, however, not due to the oxidation of ethane to ethylene by CO2; the formation of carbon monoxide in the presence Of CO2 is found to be very small. It is most probably due to the activation of ethane in the presence Of CO2.
Keywords: ethane; ethane cracking in presence Of CO2; ethane cracking in presence of CO2 and limited O-2; Ethylene; thermal cracking of ethane